Aromatherapy : Enhancement on short-term memory recall performance of DLSU-D Psychology students with different sensory modalities. - Paredes, Rose Ann T. (1998)
To find out whether aromatherapy can help enhance the short-term memory recall performance of DLSU-D AB Psychology students with different sensory modalities. After a careful analysis of the participants, the researcher concluded that there is a significant difference between aromatherapy and short-term memory recall performance. Aromatherapy works for memory enhancement. This, then, suggests that essential oils in aromatherapy acts on the mind (Lavabre, 1990) Further more it was found out that sensory modality of participants with aromatherapy did not affect their short-term memory recall performance. The scores they got had depended on how aromatherapy had worked on them and not on their sensory modality. This supports the study made by the Kevala Center : no two persons are affected by the same essential oil in exactly the same way. Aromatherapy is very individualistic.